Energy Contents of Frequently Ordered Restaurant Meals and Comparison with Human Energy Requirements and US Department of Agriculture Database Information: A Multisite Randomized Study - Urban, Lorien E.; Weber, Judith L.; Heyman, Melvin B.; Schichtl, Rachel L.; Verstraete, Sofia; Lowery, Nina S.; Das, Sai Krupa; Schleicher, Molly M.; Rogers, Gail; Economos, Christina; Masters, William A.; Roberts, Susan B. (Journal of the Academy of Nutrition and Dietetics, 2016)
Excess energy intake from meals consumed away from home is implicated as a major contributor to obesity, and ∼50% of US restaurants are individual or small-chain (non–chain) establishments that do not provide nutrition information. To measure the energy content of frequently ordered meals in non–chain restaurants in three US locations, and compare with the energy content of meals from large-chain restaurants, energy requirements, and food database information. A multisite random-sampling protocol was used to measure the energy contents of the most frequently ordered meals from the most popular cuisines in non–chain restaurants, together with equivalent meals from large-chain restaurants. Meals were obtained from restaurants in San Francisco, CA; Boston, MA; and Little Rock, AR, between 2011 and 2014. Meal energy content determined by bomb calorimetry. Regional and cuisine differences were assessed using a mixed model with restaurant nested within region×cuisine as the random factor. Paired t tests were used to evaluate differences between non–chain and chain meals, human energy requirements, and food database values. Meals from non–chain restaurants contained 1,205±465 kcal/meal, amounts that were not significantly different from equivalent meals from large-chain restaurants (+5.1%; P=0.41). There was a significant effect of cuisine on non–chain meal energy, and three of the four most popular cuisines (American, Italian, and Chinese) had the highest mean energy (1,495 kcal/meal). Ninety-two percent of meals exceeded typical energy requirements for a single eating occasion. Non–chain restaurants lacking nutrition information serve amounts of energy that are typically far in excess of human energy requirements for single eating occasions, and are equivalent to amounts served by the large-chain restaurants that have previously been criticized for providing excess energy. Restaurants in general, rather than specific categories of restaurant, expose patrons to excessive portions that induce overeating through established biological mechanisms.